Compressive property analysis and strength versus slenderness ratio relation prediction for carbon/glass hybrid fiber reinforced polymer bars. (24th January 2022) - Gao, Danying; Zhang, Yu; Fang, Dong; Ding, Chong; Yan, Huanhuan; Ji, Dongdong
Highlights: The compressive properties of carbon/glass-HFRP bars were investigated. Carbon fiber reduced the compressive strength of carbon/glass-HFRP bar. Compressive failure mode of carbon/glass-HFRP bar depended on slenderness ratio. The relations of compressive strength versus slenderness ratio were predicted. Abstract: In this paper, a total of 305 carbon/glass-hybrid fiber reinforced polymer (HFRP) bar specimens were tested under compression to systematically investigate the effects of surface configuration, volume fraction and distribution pattern of carbon fiber, total volume fraction of fiber and slenderness ratio. The results indicated that the compressive strength of carbon/glass-HFRP bars presented the varying reduction for different substitution rate of carbon fiber. The compressive strength of carbon/glass-HFRP bar specimens without end anchorage reduced averagely by 14.0% compared with those of specimens with end anchorage. Finally, the relations between compressive strength and slenderness ratio were predicted for carbon/glass-HFRP bar specimens with different characteristics.